THE INFLUENCE OF THE ECOLOGICAL CONDITIONS ON THE OCCURRENCE OF THE ECOLOGY-DEPENDENT PATHOLOGIES IN THE REGIONS OF THE REPUBLIC OF DAGESTAN - R. K.–A. Immiev; O. R. Osmanov; R. O. Osmanov (Юг России: экология, развитие, 2014)
The authors of the article research the problems of the influence of the environment and social hygienic conditions upon the population health in the Republic of Dagestan. The introduction of the developed complex of the hygienic, medical, social and economic measures promotes the improvement of the population health, the decrease of the sickness rate on the decease classes in the Republic of Dagestan.